2015
DOI: 10.1093/mnras/stv1271
|View full text |Cite
|
Sign up to set email alerts
|

Luminous red galaxies in clusters: central occupation, spatial distributions and miscentring

Abstract: Luminous Red Galaxies (LRG) from the Sloan Digital Sky Survey are considered among the best understood samples of galaxies, and they are employed in a broad range of cosmological studies. Because they form a relatively homogeneous population, with high stellar masses and red colors, they are expected to occupy halos in a relatively simple way. In this paper, we study how LRGs occupy massive halos via direct counts in clusters and we reveal several unexpected trends suggesting that the connection between LRGs a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
84
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 66 publications
10
84
3
Order By: Relevance
“…We found that the higher mass subcatalogue lacks a measurement of the pairwise kSZ signal, due to the high redshift range of the high-mass halos. Compared to the standard LRG criteria used in SDSS-I/II, the LowZ selection includes a bright magnitude cut, which excludes a significant number of low-redshift blue galaxies, but also excludes a fraction of bright galaxies in low-redshift massive clusters [46]. Figure 11 shows the redshift distribution of the lower halo mass, higher halo mass and total LowZ North CGC subcatalogues.…”
Section: E Mass Dependencementioning
confidence: 99%
“…We found that the higher mass subcatalogue lacks a measurement of the pairwise kSZ signal, due to the high redshift range of the high-mass halos. Compared to the standard LRG criteria used in SDSS-I/II, the LowZ selection includes a bright magnitude cut, which excludes a significant number of low-redshift blue galaxies, but also excludes a fraction of bright galaxies in low-redshift massive clusters [46]. Figure 11 shows the redshift distribution of the lower halo mass, higher halo mass and total LowZ North CGC subcatalogues.…”
Section: E Mass Dependencementioning
confidence: 99%
“…Using N-body simulations, Martel et al (2014) find that the fraction where the brightest galaxy is not the nearest to the centre increases from ∼25% to ∼50%, with a higher miscentring fraction towards higher mass. Hoshino et al (2015) study the distribution of LRGs in the redMaPPer clusters (Rykoff et al 2014) and find that 20-30% of the brightest LRGs are not the central galaxy. As the central galaxy might be somewhat offset from the peak of the dark matter, these results might be in agreement with our results.…”
Section: Miscentring Distributionmentioning
confidence: 99%
“…Contrary to what the name suggests, a BCG is in our adopted definition not necessarily the brightest galaxy in a cluster -it must also lie close to the cluster center as traced by the satellite galaxy distribution and/or the intracluster medium. Between 20% and 40% of central galaxies are not the brightest galaxy in their host clusters (Skibba et al 2011;Hoshino et al 2015). A famous example is M87 in the Virgo cluster.…”
Section: Introductionmentioning
confidence: 99%